DESAIN KONTROL VIBRASI SEMI AKTIF REAKSI FIXED POINT MENGGUNAKAN PENGONTROL H - Sutrisno, Sutrisno; widowati, widowati (MATEMATIKA, 2009)
The semi active fixed point reaction type of Structure Vibration Control Design contain of mass, spring, dashpot, sensor and controller. The controller in this system designed using Hâˆž method. Case study of Hard Disk Protection System make to analysis the performance of close loop system and appeal with the performance of open loop system viewed from output of simulation using MATLAB with step function and impulse function as input.